2012
DOI: 10.1377/hlthaff.2012.0402
|View full text |Cite
|
Sign up to set email alerts
|

The Post-Katrina Conversion Of Clinics In New Orleans To Medical Homes Shows Change Is Possible, But Hard To Sustain

Abstract: Hurricane Katrina destroyed much of the health care infrastructure in and around New Orleans in 2005. We describe a natural experiment that occurred afterward, amid efforts to rebuild the city's health care system, in which diverse safety-net clinics were transformed into medical homes. Using surveys of clinic leaders and administrative data, we found that clinics made substantial progress in implementing new clinical processes to improve access, quality and safety, and care coordination and integration. But t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 19 publications
(15 reference statements)
0
24
0
Order By: Relevance
“…A spate of national PCMH demonstrations focuses on different aspects of the medical home, 40 and real-world experiments are beginning to unfold under diverse conditions in preparation for implementing health reform. 30,34,41 Such variation in the goals and contexts of change are likely to lead to equally varied effects on the patient experience and other outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A spate of national PCMH demonstrations focuses on different aspects of the medical home, 40 and real-world experiments are beginning to unfold under diverse conditions in preparation for implementing health reform. 30,34,41 Such variation in the goals and contexts of change are likely to lead to equally varied effects on the patient experience and other outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…These 3 outcome measures were drawn from a wide range of items included in the patient survey, many drawn from prior studies of patient experience and satisfaction, including those reviewed above. 34 To develop the 3 indices, we inspected the distributions of all raw items in the survey for range, skewness, and central tendency (eg, medians). From this, we found that items pertaining to the more concrete aspects of the patient experience-actual behaviors and events-elicited a wider range of responses, and therefore better-differentiated patient experiences, compared with items asking for more subjective attitudes towards the clinic.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…8 As a part of that evaluation, we conducted semiannual survey telephone interviews with clinic leaders. These interviews were supplemented with routine administrative data on each clinic collected semiannually by the Louisiana Public Health Institute staff at approximately the same time.…”
Section: Methodsmentioning
confidence: 99%